REVIEW: NON-MOTOR SYMPTOMS IN DYSTONIA-PLUS DISORDERS. Issue 10 (9th September 2014) - Peall, Kathryn; Kuiper, Anouk; de Koning, Tom; Tijssen, Marina
Abstract : Objectives: Dystonia-plus and paroxysmal dyskinetic disorders are hyperkinetic movement disorders with dystonia as the predominant component. Identification of disease causing genes for these disorders has allowed examination of genetically homogenous groups. Unlike the motor symptoms, non-motor characteristics are less clearly defined. This review examines the literature pertaining to non-motor symptoms to date and identifies areas of future research. Methods: A systematic search strategy was used to review published literature relating to psychiatric disorders, cognition and sleep disturbance in genetically defined dystonia-plus and paroxysmal dyskinetic disorders. Results: Fifty-two articles were identified, the majority involving dystonia-plus disorders (n=42). Psychiatric symptoms were the most clearly defined with anxiety, depression and Obsessive-Compulsive disorder being most prominent. Cognitive impairment involved either global deficits or isolated involvement of specific domains. Sleep disturbance was documented in few disorders, being most common in the dopa-responsive dystonias. Conclusions: Results to date suggest that non-motor features form an integral component of the dystonia-plus and paroxysmal dyskinetic phenotype, with disruption to monoaminergic metabolism likely to play a central role. Further systematic and standardised assessment of these genetically homogenous cohorts is required to identify specific phenotypic characteristics. This will improve patient treatment, quality of life and our understanding of underlying pathogenesis.